PENGARUH KUALITAS PRODUK DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK CEMILAN MIE LIDI: Studi Kasus pada Konsumen Lidigeli - Azhar Abdurahman Fauzi, (2020)
This research is a quantitative study that aims to determine the effect of product quality and product design on purchasing decision of snack noodles. The population in this study is Lidigeli consumers. The sample size was taken as many as 50 respondents, with non-probability sampling methods especially purposive sampling. Data collection was carried out through questionnaires. The analysis technique used is the PLS (Partial Least Square) analysis method with SmartPLS 3.0 software. The results of this study indicate that (1) Product Quality has a significant effect on Purchasing Decisions with a path coefficient of 0,413. (2) Product design has a significant influence on purchasing decisions with a path coefficient of 0,526. R-Square purchase decision is 0,799 which means that the contribution of product quality and product design on purchase decision is 0,799 and the remaining 0,201 is influenced by other variables.